Towards more resilient food systems for smallholder farmers in the peruvian altiplano: the potential of community-based climate services - Rossa, Andrea (2020)
"Experiences from the disastrous 2016 El Niño revealed that its forecast, although available, was not known, accessed or understood by a large part of agricultural communities living in remote rural areas. This is all the more striking since these population groups are particularly vulnerable to adverse climate events as their livelihoods heavily depend on climate-sensitive agricultural production. In the framework of Climandes, a twinning project between the meteorological services of Peru and Switzerland, we implemented and evaluated the impact of community-based climate services that were co-developed with the target smallholder communities of the semi-arid highlands of the southern Peruvian Andes, where small-scale farmers are especially exposed to adverse climate events due to high inter-annual climate variability and weak socio-economic capacities. In this chapter we analyse the project implementation through a socio-economic lens. Research results generated alongside the project indicate that the well-directed user engagement resulted in a strong increase of trust in the weather service SENAMHI Peru and led to improved consideration of the information provided in the respective decision-making processes. We highlight the key steps that proved to be indispensable for the implementation of meaningful and sustainable climate services. The project outcomes point to the great and widely untapped potential of community-based climate services to reduce vulnerability and strengthen resilience of smallholder farmers in the face of changing climate conditions."